Detection and isolation of viable cancer cells mediated by spytag and spycatcher using conditionally replicative adenovirus and magnetic microbeads - Sadegh Goli; Maryam Kadkhodazadeh; Mahshid Kharaziha; Shaghayegh Haghjooy Javanmard; Kayhan Azadmanesh (Scientific Reports)
Abstract Circulating tumor cells (CTCs) are critical biomarkers for cancer diagnosis, prognosis, and therapy monitoring, but their rarity and reliance on surface markers limit detection and isolation. While conditionally replicative adenoviruses (crADs) enable tumor-selective targeting, their use has been limited to fluorescence-based detection without robust isolation of viable cells. To overcome this, we developed a crAD-based platform integrating SpyTag/SpyCatcher technology with SpyCatcher-decorated magnetic microbeads for marker-independent CTC detection and isolation. The engineered adenovirus (CR-Ad5-ST-GFP) selectively replicates in telomerase-positive tumor cells, expressing green fluorescent protein (GFP) and SpyTag under independent promoters. By leveraging the SpyTag/SpyCatcher interaction, our platform isolates CTCs without relying on surface markers, addressing epithelial-to-mesenchymal transition (EMT) and phenotype variations. In proof-of-concept experiments, A-549 and Ca Ski cells spiked into peripheral blood mononuclear cells (PBMCs) at 1:10,000 were detected and isolated with over 80% efficiency. The isolated cells remained viable and were successfully re-cultured, demonstrating their potential for downstream applications such as molecular profiling and drug sensitivity testing. This method advances crAD-based approaches by combining tumor-selective viral targeting with marker-independent, viable CTC isolation. Its compatibility with microfluidic systems makes it a promising tool for tumor monitoring and personalized cancer treatment.